Broadband and uneven spatial development: The case of Cardiff City-Region. (May 2019) - Jones, Calvin; Henderson, Dylan
The internet and e-connectivity more generally are increasingly held to be an important element of business success. Evidence however suggests that the productive impacts of such technologies are contingent on factors that include firm size and sector, and human capital. It follows that if companies with these characteristics are unevenly distributed across space, the increasing importance of broadband in economic activity might impact unevenly on economic outcomes across space. We examine the Cardiff City-Region in South Wales, where the distribution of businesses and skills suggests that without policy intervention the roll-out of broadband might further increase economic disparities between the relatively prosperous coastal belt and the poorer post-industrial hinterland.